2021
DOI: 10.1038/s41598-021-94061-3
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-27 promotes autophagy in human serum-induced primary macrophages via an mTOR- and LC3-independent pathway

Abstract: Interleukin-27 (IL-27) is a cytokine that suppresses human immunodeficiency virus (HIV)-1 infection in macrophages and is considered as an immunotherapeutic reagent for infectious diseases. It is reported that IL-27 suppresses autophagy in Mycobacterium tuberculosis-infected macrophages; however, a role for IL-27 on autophagy induction has been less studied. In this study, we investigated the impact of IL-27 in both autophagy induction and HIV-1 infection in macrophages. Primary human monocytes were differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 52 publications
0
16
1
Order By: Relevance
“…To determine whether the increased output effect was E. coli strain- or plasmid size-dependent, we compared extraction of a 15.5 kbp plasmid from the STABL3 strain (Invitrogen) [9]. STABLE3 growth was similar levels in F-Round-PP, O-Conical-PP, and F-Conical-PS and the amounts of plasmid DNA from those three tubes were comparable (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether the increased output effect was E. coli strain- or plasmid size-dependent, we compared extraction of a 15.5 kbp plasmid from the STABL3 strain (Invitrogen) [9]. STABLE3 growth was similar levels in F-Round-PP, O-Conical-PP, and F-Conical-PS and the amounts of plasmid DNA from those three tubes were comparable (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…Glycerol stock of Escherichia coli ( E. coli ) (TOP10 strain, Invitrogen, Thermo Fisher Science, Waltham, MA, USA) transformed with plasmid pCR2.1 (Invitrogen) containing 3.6 kbp DNA fragment (a total DNA size is 7.5 kbp) [8], or Stbl3 (Invitrogen) with plasmid pUC19 (Invitrogen) containing 12.8 kbp DNA (total size is 15.5 kbp) [9] was streaked on Luria-Bertani (LB) media (Quality Biological, Germantown, MD, USA)-Bacto Agar (Becton Dickinson, Franklin Lakes, NJ, USA) plate containing 100µg/ml ampicillin (MilliporeSigma, Burlington, MA, USA) (LA-plate), Five single colonies were individually inoculated in 5 mL of LA medium in 50 mL Falcon polypropylene (PP) tube (Cat# 352098) and then cultured for overnight at 37°C at 225 rpm. The next day, one % of the overnight culture was reinoculated into tubes containing warm LA (1/5 vol of each tube capacity; detail of the volume is described in the results and discussion) and cultured for 16 hr at 37°C at 225 rpm, and then, 1 mL of each bacteria suspension was subjected to isolate plasmid DNA using the S.N.A.P.…”
Section: Methodsmentioning
confidence: 99%
“…During autophagy, LC3I is decomposed to produce LC3II with a lower molecular weight, and the content of LC3II is proportional to the degree of autophagy. P62 is a specific substrate marker for autophagy, which can interact with LC3 to infiltrate into autophagosomes and effectively degrade by autophagolysosomes (Laverdure et al, 2021; Shi et al, 2019; Wu et al, 2018). The result reflected that beclin‐1 expression was significantly increased in the 80 and 160 μg/mL PM 2.5 exposure groups, indicating that autophagy was massively activated.…”
Section: Discussionmentioning
confidence: 99%
“…For example, IL-27 promoted the survival of Mycobacterium tuberculosis-infected macrophages by inhibiting autophagy [23]. Meanwhile, Laverdure et al reported that IL-27 promotes autophagy in stimulated primary human macrophages [24]. These contrasting effects of IL-27 reported in previous studies warrant further investigation into the matter.…”
Section: Neuroinflammationmentioning
confidence: 97%